Efficiency, productivity and competitiveness of the insurance industry in Malaysia and Australia - Lee, Hui Shan (2018)
The present study provides an analysis of the efficiency, productivity and competitiveness for 62 insurance firms in Malaysia and 72 insurance firms in Australia from year 2011 to 2016. The methods being utilised are Data Envelopment Analysis, Malmquist Productivity Index and Panzar-Rosse. Malaysia is experiencing insurance opportunity growth due to the expansion of population and the rising demand of Takaful insurance. Meanwhile, insurance companies in Australia is facing more competition and may cause an unsound performance. The objectives of this research are to examine the sources and development of the efficiency and productivity, identify the competitiveness of insurance market structure, analyse the effects of firms-specific factors, macroeconomics factors and globalisation factors on the performance of the insurance firms and investigate the relationship in between efficiency, productivity and competitiveness in the insurance industry. The findings postulate that inefficient insurance companies in Malaysia is caused by the scale of production rather than the inefficient use of resources due to managerial best practice. Productivity of the insurers are showing a progression trend that is attributed to technological productivity. The insurance industry in Malaysia is in the monopolistic competition market power. Insurers’ size has positive effect but commissions paid, claims liability and age seem to negatively influence the performance of insurers. On the macroeconomic factors, economic growth, interest rate and inflation are more incline to affect efficiency but less likely on productivity and competitiveness. Overall, globalisation factors are negatively influencing efficiency, positively affecting productivity and less significant to competitiveness of insurers. The influences of efficiency and productivity on competitiveness are positive and suggest that efficient and productive firms will improve competition to benefit consumers. However, the higher competition among the insurers will lead to a deterioration in efficiency.In Australia, the insurers are operating at inappropriate scale. Generally, insurers show a progressing productivity and it is attributed to technical efficiency change. Greater size, commissions paid and age generally enhance the performance of insurers but higher claims liability causes insurers to be inefficient. From the macroeconomic perspective, greater economic growth, interest rate and inflation generally hinder the performance of insurers. Generally, globalisation factors are not significant to the efficiency and competitiveness of insurers but they enhance the productivity of insurers. Strong monopolistic competition market power exists in the Australian’s insurance industry. The relationship among efficiency, productivity and competition is positive and proposes that the insurance environment in Australia encourage the competition among the insurance players to achieve comparative advantage and protect the interest of consumers. The implications of this research suggest that the insurers in Malaysia and Australia need to constantly monitor and react to the changes in macroeconomic factors. This is because, they could manage well on firms-specific factors, but the macroeconomic environments which are uncontrollable could impede their performance. Furthermore, the insurers need to understand that the effects of globalisations on the performance of insurers are different from the dimensions of economic, social and political. They are encouraged to improve efficiency, productivity and competitiveness to benefit both consumers and insurers.